Epistemic feelings, metacognition, and the Lima problem. - Greely, Nathaniel (Synthese, 2021)
Epistemic feelings like tip-of-the-tongue experiences, feelings of knowing, and feelings of confidence tell us when a memory can be recalled and when a judgment was correct. Thus, they appear to be a form of metacognition, but a curious one: they tell us about content we cannot access, and the information is supplied by a feeling. Evaluativism is the claim that epistemic feelings are components of a distinct, primitive metacognitive mechanism that operates on its own set of inputs. These inputs are heuristics that correlate with the presence of mental content that can't be accessed directly. I will argue that evaluativism is unmotivated, unsupported, and ill-conceived. I will critique the philosophical and empirical arguments for evaluativism and conclude that there is no reason to posit a distinct mechanism to explain epistemic feelings. I will conclude, however, that epistemic feelings may constitute a nonconceptual form of metacognition, which if true is a significant claim.